Rotating orifice feeding system for continuous and uniform discharge of makhana seeds (Euryale ferox). (June 2021) - Sharma, Kalyani; Patel, Shadanan; Jha, Shyam Narayan; Devi, Mridula; Vishwakarma, Rajesh Kumar
Abstract: Consistent and slow mass flow rates of granular materials through a small diameter orifice ( D ) at the center of the bottom of a hopper is difficult to obtain when D is less than 5 times of the characteristic seed size. Rotation of the bottom in the horizontal plane with the orifice placed at an off-center distance ( R ) from the center of the hopper can sustain controlled flow rates even at small D . A simple feeding system was developed in this study for discharging roasted makhana seeds of different sizes (7.48–12.40 mm diameter) at 10–30 kg h −1 consistent mass flow rates. The feeding system consists of a rotating orifice plate at an off-center distance, which is placed inside a pipe connected with the bottom of a trapezoidal hopper. The effects of rotational rate ( ω ), D, and R on the mass flow rates of makhana seeds and plastic beads of different sizes have been investigated. The materials did not discharge when the orifice was stationary. The mass flow rate increased with the increase in ω, D and R . Finite mass flow rates in the range of 2.25–29.81 kg h −1 were obtained for different seed sizes of roasted makhana seeds with varying D (15–20 mm), R (20–30 mm), and ω (0.52–7.86 rad s −1 ). The mass flow rates >30 kg h −1 were obtained at D ≥ 25 mm, however, finite mass flow rate ranges were not be obtained for all seed sizes at R ≥ 20 mm. The seed discharge was in the funnel flow regime for all D, R, ω, and seed sizes because of the geometry of the hopper and feeding system. The existing Beverloo equation did not describe the mass flow rate adequately for the developed system. Therefore, Beverloo equation was modified using a function similar to the Froude number to describe the mass flow rate. The developed feeding system performed well in feeding makhana seeds and plastic beads of different sizes and maintained finite mass flow rates. Highlights: Developed rotating orifice feeding system for consistent flow of spherical seeds in the clogged regime of orifice flow. Effects of orifice rotation rate, orifice diameter, and off-centre distance of orifice on mass flow rates were studied. Beverloo model was modified to calculate the mass flow rate in the clogged regime of orifice flow.